Aplicación de fungicidas bajo condiciones simuladas de lluvia en una plantilla de banano musa sp. en El Guabo - Morocho Illescas, Marilyn Iliana (2015)
1. The Making Río Bonito, the canton's Guabo, presents weather conditions suitable for the development of the Black Sigatoka so it is considered a hot zone, which drew objectives: To determine the effect of duration of simulation rain on the effect of the presence of infection levels of black Sigatoka and measure the effect on the infection of black Sigatoka by different sheets of water falls from rainfall simulation, for which treatments were established resulting from the combination of factors Weather (minutes) and intensity (mm) adjusted to a Design Randomized Complete bock 3x3 factorial arrangement with, the same that was analyzed by the software Statgraphic plus 5.0, adjusted with a level of confidence in the Fisher test for the analysis of the analysis of variance, and Tukey Test 95% for the comparison of pairs, so that measurements of fungal infection levels at 14, 21, 28 and 35 days were established after application of cocktail made up Strobilurin + amine (Regnum + Calixin). Emphasizing that the rainy season was who had the greater influence on the development of the fungus at the level of leaf 1 and 2, based on the results established that products applied submitted satisfactory levels d Control determining the need for a range of activities integrated management to provide synergism in the most efficient control.